2018
DOI: 10.18805/lr-3965
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic seed pelleting on seedling quality, gas exchange, growth, yield and resultant seed quality parameters of black gram

Abstract: Seed pelleting with leaf powders of two botanicals viz., pungam (Pongamia glabra) and prosopis (Prosopis juliflora) was done to study the effect of botanical seed pelleting on seedling quality, gas exchange, growth, yield and resultant seed quality parameters of black gram in the laboratory and field. From the results, it was found that, seeds pelleted with pungam leaf powder @ 150 g kg-1 recorded higher germination percentage (93.00), root length (18.35 cm), shoot length (19.34 cm), dry matter production (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The pungam leaf powder pelleting treatments might have helped in absorbing more soil moisture and nutrients, thus enabling better growth resulting in higher yield (Sai Pradeep Kumar, 2015). Similar observations with increased yield parameters due to seed pelleting under saline condition were reported by Harish Babu et al(2005 and Prakash et al (2018). Increased pod yield was observed which may be due to the translocation of sugars from complex compounds like carbohydrates which are translocated at greater rate as reported by Dileepkumar et al (2009).The influence of seed hardening with CaCl 2 and KCl observed in present results are in line with the reports of Mishra and Dwivedi (1980) and Sen and Misra (1987).…”
Section: Yield Parameterssupporting
confidence: 88%
See 4 more Smart Citations
“…The pungam leaf powder pelleting treatments might have helped in absorbing more soil moisture and nutrients, thus enabling better growth resulting in higher yield (Sai Pradeep Kumar, 2015). Similar observations with increased yield parameters due to seed pelleting under saline condition were reported by Harish Babu et al(2005 and Prakash et al (2018). Increased pod yield was observed which may be due to the translocation of sugars from complex compounds like carbohydrates which are translocated at greater rate as reported by Dileepkumar et al (2009).The influence of seed hardening with CaCl 2 and KCl observed in present results are in line with the reports of Mishra and Dwivedi (1980) and Sen and Misra (1987).…”
Section: Yield Parameterssupporting
confidence: 88%
“…Similarly, increased gas exchange parameters due to flyash treatment was reported by Anbarasan (2011) in cowpea. Prakash et al (2018) found that plants treated with pungam leaf powder @ 150 g kg -1 recorded more photosynthesis, transpiration rates and stomatal conductance. Increase in gas exchange parameters might be due to increased enzyme activity, chlorophyll content and presence of growth promoting substances like GA 3 which leads to more production of photo-assimilates and better growth and development (Prakash et al, 2018).…”
Section: Physiological Parametersmentioning
confidence: 92%
See 3 more Smart Citations